2017
DOI: 10.3892/ijmm.2017.3312
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament‑associated protein‑1 delays rat periodontal bone defect repair by regulating osteogenic differentiation of bone marrow stromal cells and osteoclast activation

Abstract: The aim of the present study was to assess the roles of periodontal ligament‑associated protein‑1 (PLAP‑1) in the osteogenic differentiation of rat bone marrow stromal cells (rBMSCs) and in osteoclast activation during the repair of rat periodontal bone defects. Male, 6‑week‑old, Wistar rats treated with periodontal bone defects were randomly assigned to 3 groups: The PLAP‑1‑transfected rBMSC group (PLAP‑1 group), the empty vector‑transfected rBMSC group (vector group) and the normal rBMSC group (control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
3
8
1
Order By: Relevance
“…also reported that ASPN treatment inhibited ALP intensity and activity and decreased the expression levels of osteogenesis‐related COL1A1, thereby inhibiting the cytodifferentiation and mineralization of periodontal ligament cells 39 . Another study reported that ASPN overexpression decreased OCN expression in rat periodontal bone defects 40 . The just‐mentioned documentations further increased the credibility of our results.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…also reported that ASPN treatment inhibited ALP intensity and activity and decreased the expression levels of osteogenesis‐related COL1A1, thereby inhibiting the cytodifferentiation and mineralization of periodontal ligament cells 39 . Another study reported that ASPN overexpression decreased OCN expression in rat periodontal bone defects 40 . The just‐mentioned documentations further increased the credibility of our results.…”
Section: Discussionsupporting
confidence: 76%
“…39 Another study reported that ASPN overexpression decreased OCN expression in rat periodontal bone defects. 40 The just-mentioned documentations further increased the credibility of our results. Meanwhile, a decrease in HAPLN1 expression was accompanied by an increase in COL1A1 expression in damaged cartilage, 41 which indirectly supports our finding in this study that COL1A1 expression was upregulated after HAPLN1 knockdown in BMSCs of OVX mice.…”
Section: High Expression Of Aspn and Hapln1 In Opsupporting
confidence: 61%
“…This mechanical property is called thixotropy and has been attributed to proteoglycans in skin (Finlay, 1978). Asporin regulates PDL fibroblasts (Kajikawa et al, 2014) via BMP-2 and PDL osteoclasts via receptor activator of nuclear factor κB ligand (RANKL) and osteoprotegerin (OPG) (Yu et al, 2018) as well as negative regulation of TGF-β (Kizawa et al, 2005) and bone morphogenetic protein 2 (BMP-2) (Yamada et al, 2008) and enhancement of fibroblast growth factor 2 (FGF-2) (Awata et al, 2015). Asporin's regulation of osteogenic growth factors is in line with our results showing localization near the alveolar bone side of the PDL and in the bone itself.…”
Section: Discussionmentioning
confidence: 99%
“…Proteoglycans contribute to maintaining the structure of the tissue and the ECM and protect the integrity in the face of heavy loading, for example in intervertebral disks (Roughley, 2006), in tendons (Screen et al, 2006), and in the PDL (Kurylo et al, 2016). Beyond their mechanical function, they also modulate growth factors (Zhang et al, 1995;Häkkinen et al, 2000;Kizawa et al, 2005;Yamada et al, 2008;Awata et al, 2015;Yu et al, 2018) and regulate ECM composition and structure (Matheson et al, 2005;Chen and Birk, 2013;Kurylo et al, 2016). Gylcoproteins are proteins with covalently attached N-linked glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal ligament‐associated protein 1 (PLAP‐1/asporin) is an extracellular matrix protein preferentially expressed in periodontal ligament (PDL) and an important regulator of osteogenic differentiation of periodontal ligament cells . PLAP‐1 is involved in the homeostasis of periodontal tissues and protects the periodontal ligament from excessive osteogenesis .…”
Section: Introductionmentioning
confidence: 99%